2018
DOI: 10.1163/1572543x-12341489
|View full text |Cite
|
Sign up to set email alerts
|

Experiences of (Mis)recognition of Same-Sex Partnerships in the Evangelical Lutheran Church of Finland

Abstract: The article discusses the recognition of same-sex partnerships in the Evangelical Lutheran Church of Finland (ELCF). The main focus is on the experiences of recognition and misrecognition of same-sex couples when the couples have asked for a prayer on behalf of their registered partnership. The findings of this study confirm that the researched experiences of recognition have two dimensions, vertical and horizontal. Vertical recognition deals with institutional recognition and experiences with the sacred. Hori… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 0 publications
0
2
0
1
Order By: Relevance
“…R340 argued, "There must be space for all members of a congregation". An early study showed that same-sex couples often have negative experiences of misrecognition from the institutional ELCF (Hellqvist and Vähäkangas 2018). As I presented above, opposite-sex marriage is sacred for the opponents of same-sex marriage.…”
Section: Theological Justificationsmentioning
confidence: 98%
“…R340 argued, "There must be space for all members of a congregation". An early study showed that same-sex couples often have negative experiences of misrecognition from the institutional ELCF (Hellqvist and Vähäkangas 2018). As I presented above, opposite-sex marriage is sacred for the opponents of same-sex marriage.…”
Section: Theological Justificationsmentioning
confidence: 98%
“…The Church institution, in turn, has power to influence and maintain these cultural habits in defining death rituals and maintaining the vast majority of Finnish cemeteries, guiding also how lost people can be honoured in gravesite memorials. Given the tense relationship between LGBTQ people and the Church institution in Finland, resulting from the inability of the Church to treat LGBTQ people with "fully equal respect" (Hellqvist & Vähäkangas 2018), I argue that having to face this prioritised role of the Church can be challenging for bereaved LGBTQ people, regardless of their personal worldviews. However, I do not claim that the Finnish culture of death is a monolith with no variation nor a possibility to change and be altered.…”
Section: Culture(s) Of Death In Finlandmentioning
confidence: 99%
“…Att synen på homosexualitet är splittrad känns igen från tidigare studier; forskare från olika länder betonar att homosexualitet är den mest centrala skiljelinjen mellan liberala och värdekonservativa kyrkor idag (se exempelvis Hellqvist & Vähäkangas, 2018;Woodhead, 2007). De olika synsätten skapar konflikter och splittringar såväl mellan som inom samfunden (Carlström, 2020;van den Berg, 2017).…”
Section: Lena Roos Professor I Religionsvetenskapunclassified